Acoustofluidic platforms for particle manipulation. Issue 7 (12th November 2021) - Novotny, Jakub; Lenshof, Andreas; Laurell, Thomas
Abstract: There is an increasing interest in acoustics for microfluidic applications. This field, commonly known as acoustofluidics involves the interaction of ultrasonic standing waves with fluids and dispersed microparticles. The combination of microfluidics and the so‐called acoustic standing waves (ASWs) led to the development of integrated systems for contact‐less on‐chip cell and particle manipulation where it is possible to move and spatially localize these particles based on the different acoustophysical properties. While it was initially suggested that the acoustic forces could be harmful to the cells and could impact cell viability, proliferation, or function via phenotypic or even genotypic changes, further studies disproved such claims. This review is summarizing some interesting applications of acoustofluidics in the manipulations of biomaterials, such as cells or subcellular vesicles, in works published mainly within the last 5 years.